Multitasking Without Thrashing. - Denning, Peter J. (Communications of the ACM, 2017)
The article discusses multitasking in the context of information technology (IT) in relation to the functioning of operating systems. Topics include the Getting Things Done (GTD) system developed by author David Allen in his book by that title, the functioning of operating systems (OSs) for computer processing units (CPUs), and the evaluation of tasks.